(untitled) (Perner’s Contacts, 2020)
In 1956, an important document in the field of road freight transport was adopted - the CMR Convention. Its adoption unified certain rules in the international carriage of goods. This unified in particular the accompanying documentation of the consignment and the liability of the road carrier. Since the adoption of the CMR Convention, the method of calculating the liability of the carrier, which has introduced the Protocol to the CMR Convention, has changed. The Protocol changed the system for calculating liability from a gold franc to a system based on special drawing rights. The accompanying documentation is unified in road freight transport in the form of a CMR consignment note. In recent years, carriers have been required to neutralize this accompanying document. It has been shown that neutralization of the consignment note is used in some cases for fraud on the consignor. The aim of the paper is to determine the impact of the use of neutralization of the CMR consignment note on the liability of the carrier and the attitude of the insurance company towards the carrier in case of proving the neutralization of the CMR consignment note. As the adoption of the Protocol is not a matter of course, there are the Member States of the Convention which have not accepted the Protocol. Given that there are currently two ways of limiting the liability of a road carrier, we also want to point out the importance of adopting the Protocol to the CMR Convention and its impact on competitiveness if the carrier is exposed to the risk of neutralization.